2020
DOI: 10.1073/pnas.1919490117
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of the cell-binding component of the Clostridium difficile binary toxin reveals a di-heptamer macromolecular assembly

Abstract: Targeting Clostridium difficile infection is challenging because treatment options are limited, and high recurrence rates are common. One reason for this is that hypervirulent C. difficile strains often have a binary toxin termed the C. difficile toxin, in addition to the enterotoxins TsdA and TsdB. The C. difficile toxin has an enzymatic component, termed CDTa, and a pore-forming or delivery subunit termed CDTb. CDTb was characterized here using a combination of single-particle cryoelectron microscopy, X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 64 publications
5
53
0
Order By: Relevance
“…b The secondary structure of RBD2 predicted from the chemical shift index method is illustrated and consists of 8 beta strands (β1, I767-N775; β2, T781-A789; β3, Q802-T809; β4, K816-N827; β5, T837-N841; β6, I852-Y855; β7, K857-I863; β8, R868-V875) shown with blue arrows and 2 alpha helices (α1, D758-A764; α2, K795-Y800) highlighted in red. The remaining regions of RBD2 are predicted to exist as random coil and are shown with a black line in the secondary structure representation CSI analyses predicts that the RBD domain has eight beta strands (I767-N775; T781-A789; Q802-T809; K816-N827; T837-N841; I852-Y855; K857-I863; R868-V875) and 2 alpha helices (D758-A764; K795-Y800), which is fully consistent with the X-ray and cryoEM structures reported previously (Xu et al 2020). In summary, the chemical shift values for backbone and sidechain resonances of RBD2 obtained here were deposited in the Biological Magnetic Resonance Bank database (http://www.bmrb.wisc.edu) under accession number 28,131, and these data will be important for nextstage NMR studies that map RBD2 biomolecular interactions and for developing inhibitors targeting CDTb.…”
Section: Extent Of Assignment and Data Depositionsupporting
confidence: 88%
“…b The secondary structure of RBD2 predicted from the chemical shift index method is illustrated and consists of 8 beta strands (β1, I767-N775; β2, T781-A789; β3, Q802-T809; β4, K816-N827; β5, T837-N841; β6, I852-Y855; β7, K857-I863; β8, R868-V875) shown with blue arrows and 2 alpha helices (α1, D758-A764; α2, K795-Y800) highlighted in red. The remaining regions of RBD2 are predicted to exist as random coil and are shown with a black line in the secondary structure representation CSI analyses predicts that the RBD domain has eight beta strands (I767-N775; T781-A789; Q802-T809; K816-N827; T837-N841; I852-Y855; K857-I863; R868-V875) and 2 alpha helices (D758-A764; K795-Y800), which is fully consistent with the X-ray and cryoEM structures reported previously (Xu et al 2020). In summary, the chemical shift values for backbone and sidechain resonances of RBD2 obtained here were deposited in the Biological Magnetic Resonance Bank database (http://www.bmrb.wisc.edu) under accession number 28,131, and these data will be important for nextstage NMR studies that map RBD2 biomolecular interactions and for developing inhibitors targeting CDTb.…”
Section: Extent Of Assignment and Data Depositionsupporting
confidence: 88%
“…It was demonstrated that also CDTb forms pores in lipid bilayer membranes in vitro (Kronhardt et al, 2017). More recently, it was shown that CDTb forms di-heptamer like structures (Xu et al, 2020). Furthermore, when applied to cells, CDTb alone (in the absence of CDTa) is able to cause dramatic changes in cell morphology and cell viability (Kronhardt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the ‘A’ subunit binds to the ‘B’ oligomer complex in all binary toxins prior to being endocytosed and trafficked into endosomes. While the ‘A’ subunit is monomeric for each binary toxin, the oligomeric structure has been shown to consist of varying compositions including heptameric, octameric, as well as di-heptamer associations of singly processed ‘B’ subunits [ 19 , 20 ]. Likewise, it is hypothesized that a conformational shift in the ‘B’ subunit assembly, facilitated by the acidic pH of the endosomal compartment, induces translocation of the ‘A’ subunit into the host cytosol where the host NAD + /NADPH acts as a donor for catalytic transfer of ADP-ribose to monomeric G-actin.…”
Section: Cdt Structure and Mechanism Of Actionmentioning
confidence: 99%
“…Limited chymotrypsin proteolysis of pro-CDTb is sufficient to remove the signaling peptide (SD; residues 1–43) and the activation domain (AD; residues 44–211) yielding an oligomeric and active form of CDTb (residues 212–876; Figure 3 A,B) [ 15 ]. Unlike the heptameric and octomeric states identified for the cell-binding components of other bacterial binary toxins such as anthrax and iota toxins, CDTb was shown by single-particle cryoEM micrsoscopy to fold into two unique di-heptameric structures (~1.0 MDa) including a symmetric and an asymmetric dimer of heptamers, solved at resolutions of 3.14 Å ( Sym CDTb) and 2.84 Å ( Asym CDTb), respectively [ 20 ]. A corroborative study confirmed these data at a lower resolution and were given names as ‘short’ and ‘long’ particles, corresponding to the asymmetric ( Asym CDTb) and symmetric ( Sym CDTb) di-heptamers, respectively ( Figure 3 C and 3D) [ 37 ].…”
Section: Cdt Structure and Mechanism Of Actionmentioning
confidence: 99%